A STUDY ON AN EFFECT OF THE GREEN TEA EXTRACT ON QUALITY AND SHELF LIFE OF ANIMAL FATS DURING STORAGE - Konstantin A. Lehukov; Sergei S. Tsikin (Теория и практика переработки мяса, 2020)
An analysis of an effect of the green tea extract on quality and shelf life of animal fats is presented. It is shown that the rate and depth of fat hydrolysis depend on a storage temperature. The higher the storage temperature, the higher the rate of fat hydrolysis and, consequently, the acid value. During storage for more than 3 days at any temperature, fats (except mutton fat) begin to change their properties. Mutton fat shows the first signs of spoilage (an increase in the acid value of more than 2.2 mg КОН, MAC ND) after 10 days of storage. An insignificant variation in the peroxide value of all tested fats during 10 days of storage, which was within the range of MAC, was established. After 10 days of storage, the rate of formation of peroxides and hydroperoxides rose sharply, which was confirmed by the peroxide value of these fats. Addition of antioxidants of the green tea extract in an amount of 10 g per 100 kg fat ensured appropriate storage of all fat types upon storage conditions that corresponded to the normative and technical documentation.